MEASURING AND MODELING INTERGENERATIONAL LINKS IN RELATION TO LONG‐TERM CARE. (12th August 2016) - Caplin, Andrew; Luo, Mi; McGarry, Kathleen
Abstract : Long‐term care has profound intergenerational implications. It can be costly for those who need it and onerous for loved ones who provide it. We pinpoint three intergenerational aspects of long‐term care that require further research. One concerns the link between costs of private care and intergenerational wealth transfers. The second concerns the link between participation in care and the work and welfare of family providers. The third relates to intergenerational tensions that these and other late‐in‐life interactions create. We outline innovations in modeling and measurement that would improve understanding of intergenerational linkages and their implementation in appropriate panel data. ( JEL D91, I13, J22)